Serious Psychological Distress and Diabetes Management among American Indians and Alaska Natives - Huyser, Kimberly R. (Ethn Dis, 2015)
OBJECTIVE: This paper examined associations between serious psychological distress and blood glucose level (HbA(1)C) and Body Mass Index (BMI) among American Indian and Alaska Native (AI/AN) participants in a cardiovascular disease prevention program. DESIGN: Using linear regression, we assessed the relationships between serious psychological distress and HbA(1)C and BMI at baseline and one-year later. Setting, Participants, and Intervention: AI/AN participants were 18 years or older, diagnosed with Type 2 diabetes, and enrolled in the Special Diabetes Project for Indians - Healthy Heart Project. MAIN OUTCOME MEASURES: Outcomes were percentage of HbA(1)C and BMI, measured at enrollment and first annual exam. Both outcomes were continuous measures in all analyses. RESULTS: Serious psychological distress was associated at baseline with increased HbA(1)C in the unadjusted and adjusted models (adjusted b=0.17%, p< 0.01). Serious psychological distress also was associated at baseline with increased BMI (0.635 kg/m(2), p = 0.01) and at one-year with increased BMI (0.174 kg/m(2), p = 0.01) in the unadjusted model. After adjustment for demographic and health characteristics, these relationships were no longer significant. CONCLUSIONS: Cross-sectional baseline findings are consistent with existing literature. One-year findings suggest need for further inquiry into mediators of psychological distress and examination of additional diabetes-specific health outcomes. Additional years of observation may be needed to disentangle relationships between serious psychological distress and BMI.